2015
DOI: 10.1071/is14056
|View full text |Cite
|
Sign up to set email alerts
|

Morphological phylogenetics of the Tenthredinidae (Insecta : Hymenoptera)

Abstract: The Tenthredinoidea is the most diverse superfamily of non-apocritan Hymenoptera. It is also one of the largest herbivorous groups within the order, some species having substantial economic impact. Until very recently, no comprehensive phylogenetic analyses of the superfamily had been undertaken. This paper presents the largest morphological dataset assembled so far for elucidating the phylogeny of the Tenthredinoidea. In total, 129 taxa were scored for 146 characters from the adult head, thorax, wings and ovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…The CAP clade has been retrieved by other morphological analyses (e.g. Vilhelmsen, , ), but not by molecular or combined analyses, which have placed Cimbicidae as sister to Diprionidae (Schulmeister, ; Schmidt & Walter, ; Isaka & Sato, ; Malm & Nyman, ) or a clade including Diprionidae (Heraty et al ., ; Ronquist et al ., ; Klopfstein et al ., ). These studies all have very incomplete sampling of Cimbicidae; Malm & Nyman () which otherwise has the most comprehensive sample of the family (five genera, eight species) did not include any South American cimbicids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CAP clade has been retrieved by other morphological analyses (e.g. Vilhelmsen, , ), but not by molecular or combined analyses, which have placed Cimbicidae as sister to Diprionidae (Schulmeister, ; Schmidt & Walter, ; Isaka & Sato, ; Malm & Nyman, ) or a clade including Diprionidae (Heraty et al ., ; Ronquist et al ., ; Klopfstein et al ., ). These studies all have very incomplete sampling of Cimbicidae; Malm & Nyman () which otherwise has the most comprehensive sample of the family (five genera, eight species) did not include any South American cimbicids.…”
Section: Resultsmentioning
confidence: 99%
“…The monophyly of Cimbicidae has never been contested; indeed, it is well corroborated in the present study, as well as most recent phylogenetic studies with more than one representative of the family included (Schulmeister, ; Ronquist et al ., ; Malm & Nyman, ; Vilhelmsen, ; see, however, Isaka & Sato, ). The antennal club (char.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third set, congruence between the evolution of ferns and sawflies was explored by plotting the distribution of pteridophagy and the ferns used across the phylogeny of sawfly families (Malm & Nyman, 2015) and the phylogeny of fern orders . The three pteridophagous clades were also recognized in the phylogenetic hypothesis based on morphological characters only, although this study reported slightly different relationships among the main clades of the Tenthredinidae (Vilhelmsen, 2015).…”
Section: Methodsmentioning
confidence: 88%
“…In recent years, the improved understanding of the early diversification of angiosperms provided new opportunities to study the "co-diversification" of angiosperms and phytophagous insects (Ehrlich & Raven, 1964;Jermy, 1984;De Vienne et al, 2013;Althoff et al, 2014;Hembry et al, 2014;Suchan & Alvarez, 2015). Increasing attention has been given to the hypothesis that the diversification of phytophagous insects coincided with the rapid rise of angiosperms during the Cretaceous Terrestrial Revolution (KTR) (McKenna et al, 2009;Wang et al, 2013;Donovan et al, 2014;Kergoat et al, 2014;Labandeira, 2014;Isaka & Sato, 2014a, 2014b, 2015. The replacement of "gymnosperm-dominated forests" by "angiosperm-dominated forests" is widely considered to be one of the main factors creating the unequal distribution of herbivorous insects across the phylogeny of plants, one facet of which is the low diversity of exclusively pteridophagous (fern-feeding) insects (Balick et al, 1978;Hendrix, 1980;Ottosson & Anderson, 1983;Jermy, 1984;Cooper-Driver, 1985;Weintraub et al, 1995;Ward et al, 2003).…”
mentioning
confidence: 99%